Time Horizon: Intersections of Deep Time and Biographical Time on the West Shore, Stromness, Orkney. Issue 2 (1st December 2021) - Irvine, Richard D. G.; Downing, Niamh; Bevan, Anne; Fearnley, Carina
Abstract : What is the significance of a human life in relation to the timespan of the geological processes that shape and reshape the terrain under our feet? Here, we ask how we might think on a planetary scale while being grounded in the everyday, tracing the relationship between biographical time and geological formation. Examining social relationships through the materiality of sandstone, uranium, and concrete, this paper presents a collaborative deep time practice, realized through the iterative process of walking, reading and inscribing a specific site, the West Shore of Stromness, Orkney.